THE COMPONENT ELEMENTS OF THE ENTERPRISES ECONOMIC SECURITY ASSESSMENT DETERMINATION: SCIENTIFIC AND METHODOLOGICAL APPROACHES AND TOOLS - NYZHNYK, Viktor; NYZHNYK, Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Commonly accepted approaches to the diagnosis of the system of economic security of industrial enterprises describe the trends and complex impact and reveal the coordinated combination of methodological tools of analysis. However, a general assessment of economic security must be preceded by a structural analysis in terms of its provision, and this is the key problematic point - the vast majority of authors have their own vision of the composition of the elements of the economic security of the enterprise, and, therefore, the elements of its assessment, which leads to significant inaccuracies and inconsistencies in the case of using several different methods in the system of assessing the economic security of the enterprise.The purpose of this study is to consider the main methodological approaches to the assessment of the economic security of the enterprise and the tools used within them, and the formation of an innovative toolkit and elements of economic security assessment based on its results.In the course of the study, were highlighted the features and shortcomings of generally accepted approaches in assessing the economic security of the enterprise. Systematized available methodical approaches by general, structural, factor and individual groups. Carried out the formalization of general approaches to the diagnosis of the state and development opportunities of the system of economic security of industrial enterprises in conditions of competition by process, strategic and system approaches has been. The methodical toolkit for comprehensive assessment of the state and development prospects of the system of economic security of industrial enterprises is outlined.
Keywords: economic security; assessment; methods; tools; constituent elements; scientific and methodical approaches